2014
DOI: 10.1200/jco.2013.51.7433
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Duration of Low Molecular Weight Heparin for the Treatment of Cancer-Related Deep Vein Thrombosis: The Cancer-DACUS Study

Abstract: In patients with cancer with a first DVT, treated for 6 months with LMWH, absence of RVT identifies a population at low risk for recurrent thrombotic events. Continuation of LMWH in patients with RVT up to 1 year did not reduce recurrent VTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 25 publications
0
67
1
1
Order By: Relevance
“…The updated search identifi ed one study 47 that assessed extended LMWH treatment in patients with cancer and residual VTE after an initial 6 months of nadroparin (97 IU/kg twice a day). Patients with residual VTE were randomly assigned to either 6-month anticoagulation continuation (119 patients) or immediate anticoagulant discontinuation (123 patients).…”
Section: Early Maintenance (10 Days To 3 Months) and Long-term (Beyonmentioning
confidence: 99%
“…The updated search identifi ed one study 47 that assessed extended LMWH treatment in patients with cancer and residual VTE after an initial 6 months of nadroparin (97 IU/kg twice a day). Patients with residual VTE were randomly assigned to either 6-month anticoagulation continuation (119 patients) or immediate anticoagulant discontinuation (123 patients).…”
Section: Early Maintenance (10 Days To 3 Months) and Long-term (Beyonmentioning
confidence: 99%
“…3,26 The recurrence rate at 5 years has not been estimated given the high cancer mortality by 5 years. In the DACUS study, 27 an additional 6 months of anticoagulation was found to reduce the risk of DVT recurrence in patients who had residual DVT on ultrasound imaging following their initial 6 months of anticoagulation. However, this reduction in recurrent VTE risk was lost once anticoagulation had been stopped.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…The adoption of an algorithm incorporating both RVT and serial D-Dimer was found to identify a substantial proportion of patients with unprovoked DVT in who anticoagulation can be safely discontinued (annual rate of recurrent VTE, 3.0%). According to recent findings, RVT can be of help for predicting the risk of recurrent VTE also in patients with cancer [19].…”
Section: Issn: 2380-6842mentioning
confidence: 96%